Changes in the Upper and Lower Pharyngeal Airway Spaces Associated with Rapid Maxillary Expansion. (18th June 2012) - Aloufi, Fitin; Preston, Charles B.; Zawawi, Khalid H.
Abstract : Objectives . The primary objectives of this retrospective study were first to compare the upper and lower pharyngeal airway spaces between orthodontic patients with and without maxillary constriction and second to evaluate the effect of rapid maxillary expansion (RME) on these airway spaces. A secondary objective was to compare the mode of breathing between groups. Materials and Methods . The experimental (RME) group consisted of 30 patients (mean age, 14.2 ± 1.3 years, 16 boys and 14 girls) with maxillary constriction who were treated with hyrax-type RME. The control group comprised the records of age- and gender matched patients (mean age, 13.8 ± 1.5 years, 16 boys and 14 girls) with no maxillary constriction but requiring nonextraction comprehensive orthodontic treatment. Cephalometric measurements in the sagittal dimension of upper and lower airway spaces for the initial and final records were recorded. Mode of breathing and length of treatment were also compared. Results . The sagittal dimension of the upper airway increased significantly in the RME group (mean = 1.3 mm) compared to the control group (mean = 0.5 mm), P = 0.016 . However, there was no significant difference in the lower pharyngeal airway measurement between the RME group (mean = 0.2 ) and the control group (mean = 0.4 ), P = 0.30 . There was no significant difference with respect to mode of breathing between the two groups (P = 0.79 ). Conclusion . Rapid maxillary expansion (RME) during orthodontic treatment may have a positive effect on the upper pharyngeal airway, with no significant change on the lower pharyngeal airway.